Laboratory Accuracy Improvement in the UK NEQAS Leucocyte Immunophenotyping Immune Monitoring Program: An Eleven‐Year Review via Longitudinal Mixed Effects Modeling. Issue 2 (16th May 2017) - Bainbridge, John; Rountree, Wes; Louzao, Raul; Wong, John; Whitby, Liam; Denny, Thomas N.; Barnett, David
Abstract : Background: The United Kingdom National External Quality Assessment Service (UK NEQAS) for Leucocyte Immunophenotyping Immune Monitoring Programme, provides external quality assessment (EQA) to non‐U.S. laboratories affiliated with the NIH NIAID Division of AIDS (DAIDS) clinical trials networks. Selected laboratories are required to have oversight, performance monitoring, and remediation undertaken by Immunology Quality Assessment (IQA) staff under the DAIDS contract. We examined whether laboratory accuracy improves with longer EQA participation and whether IQA remediation is effective. Methods: Laboratory accuracy, defined by the measurement residuals from trial sample medians, was measured on four outcomes: both CD4+ absolute counts (cells/μL) and percentages; and CD8+ absolute counts (cells/μL) and percentages. Three laboratory categories were defined: IQA monitored ( n = 116), United Kingdom/non‐DAIDS ( n = 137), and non‐DAIDS/non‐UK ( n = 1034). For absolute count outcomes, the groups were subdivided into single platform and dual platform users. Results: Increasing EQA duration was found to be associated with increasing accuracy for all groups in all four lymphocyte subsets ( P < 0.0001). In the percentage outcomes, the typical IQA group laboratory improved faster than laboratories from the other two groups ( P < 0.005). No difference in the overall rate of improvement was found between groups for absolute count outcomes. However, in the DPT subgroup the IQA group ultimately showed greater homogeneity. Conclusions: EQA participation coupled with effective laboratory monitoring and remedial action is strongly associated with improved laboratory accuracy, both incrementally and in the proportion of laboratories meeting suggested standards. Improvement in accuracy provides more reliable laboratory information facilitating more appropriate patient treatment decisions. © 2017 International Clinical Cytometry Society